1988
DOI: 10.1007/bf01889016
|View full text |Cite
|
Sign up to set email alerts
|

Gastric hamartomatous polyp without polyposis coli: Radiologic diagnosis

Abstract: Gastric hamartomatous polyps were found in 25 patients over a period of 4 1/2 years, for an incidence of 11% in all endoscopically biopsied polyps. The number of polyps was fewer than 5 in most patients. All polyps were sessile, sharply demarcated, hemispheric protrusions, measuring up to 10 mm in diameter but most were less than 5 mm. The most characteristic finding differing from hyperplastic polyps, adenoma, and polypoid carcinoma was that hamartomatous polyps were located in the fundic gland mucosa, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Gastric hamartomatous polyps are rare, being found in less than 0.1% of all endoscopic examinations. [15][16][17] Only 27 cases of gastric hamartomatous polyps have been reported in Japan, including our case. There does not seem to be any gender preponderance and the patients ranged in age from 8 to 85 years old.…”
Section: Discussionmentioning
confidence: 85%
“…Gastric hamartomatous polyps are rare, being found in less than 0.1% of all endoscopic examinations. [15][16][17] Only 27 cases of gastric hamartomatous polyps have been reported in Japan, including our case. There does not seem to be any gender preponderance and the patients ranged in age from 8 to 85 years old.…”
Section: Discussionmentioning
confidence: 85%
“…Most studies have also shown a similar age range (11,12,16,17). Although many studies have reported a female predominance (11,12,14,16,17,19), other studies have not (15).…”
Section: Discussionmentioning
confidence: 91%
“…This selection criterion was based on a review of the (scant) literature that reported the distribution of polyps per case in the setting of patients on proton pump inhibitors (PPI), which suggested a possible bimodal distribution (15), with the number of 10 polyps as a potentially useful discriminator between those with and without SFGP. This potential bimodal distribution is less apparent in studies of patients that were conducted before the widespread use of PPI (11,12,16,17).…”
mentioning
confidence: 94%
“…Solitary hamartomatous polyps of stomach are rare in adult, found in less than 0.1% of all endoscopic examinations . The differential diagnosis includes solitary juvenile polyps and Peutz‐Jeghers‐type polyps .…”
Section: Take Home Messagementioning
confidence: 99%